A Software Decoding Error Compensation Method for Resolvers in Automotive Electric Drive Systems - GUO Zhida; CHEN Zhichu; TANG Xionghui; LIU Wang; LI Jing; CHEN Zuoling (Kongzhi Yu Xinxi Jishu)
In automotive electric drive systems, software decoding based on Delta-Sigma Analog-to-Digital Converter (DSADC) for resolvers is associated with angular errors. To address this challenge, this paper analyzes the influence of different integration starting times on the angle output from decoding. Based on a mathematical model established to correlate integration starting times with angular errors in the decoding outputs, an analytical expression is derived for angular errors as a function of integration starting time, which establishes a direct proportional relationship between the two. Consequently, the paper proposes an angular error compensation method covering the entire speed range of resolvers, based on speed normalization. Simulations conducted on a hardware-in-the-loop (HIL) experimental platform based on dsPACE verify that the proposed method is effective in compensating for angular errors caused by varying integration times. This approach offers a solution to the inconsistent product performance resulting from device parameter differences in the mass production of resolver software decoding products.